The unmet needs of informal carers of stroke survivors: a protocol for a systematic review of quantitative and qualitative studies. Issue 1 (31st January 2018) - Denham, Alexandra M J; Baker, Amanda L; Spratt, Neil; Guillaumier, Ashleigh; Wynne, Olivia; Turner, Alyna; Magin, Parker; Bonevski, Billie
Abstract : Introduction: Stroke events deeply affect not only the stroke survivor but also often the quality of life and physical and psychological health of the family and friends who care for them. There is a need for further information about the unmet needs of these informal carers in order to develop support services and interventions. The primary objective of this review is to report and synthesise the research describing the unmet needs of carers of stroke survivors. Methods and analysis: A systematic review of quantitative and qualitative studies that report on the unmet needs of carers will be conducted. The following databases will be searched for relevant articles: MEDLINE, Cumulative Index to Nursing and Allied Health Literature, PsycINFO, EMBASE, Allied and Complementary Medicine Database and Scopus. No publication date constraints will be applied. Studies will be limited to those published in English and conducted among humans. Eligible studies will report on the unmet needs of informal carers of stroke survivors, defined as family members, friends and other unpaid caregivers. Studies which focus on formal, clinical or medical caregivers will be excluded. A narrative synthesis and pooled analysis of the main outcomes will be reported. Ethics and dissemination: This review will be submitted to a peer-reviewed journal. Our findings are expected to provide new insights into the unmet needs of stroke survivors' carers. Knowledge about the unmet needs of carers will inform the development and refinement of interventions and services to address these needs and better support carers of stroke survivors. The findings of this systematic review will be disseminated publicly and in peer-reviewed journals and may be the topic of research presentations. Trial registration number: CRD42017067391 .